The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1097/ta.0000000000000736
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxemia during aeromedical evacuation of the walking wounded

Abstract: Epidemiologic/prognostic study, level V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…In the latest guidelines, hyperoxemia is defined as an S pO 2 > 94% for the general population and > 92% for patients with COPD. [5][6][7][8][9][11][12][13][14][15][16][17]19 An S pO 2 target of 88-92% reduced mortality in patients with respiratory distress in comparison with current practices of an S pO 2 frequently > 92% and oxygen flows ranging from 8 to 15 L/min. 8,9,10,15,19 In most cases, the frequent liberal use of oxygen leads to detrimental consequences, 6,7,9,11,14,17,[19][20][21][22] particularly in patients with trauma or respiratory distress and during myocardial infarction.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…In the latest guidelines, hyperoxemia is defined as an S pO 2 > 94% for the general population and > 92% for patients with COPD. [5][6][7][8][9][11][12][13][14][15][16][17]19 An S pO 2 target of 88-92% reduced mortality in patients with respiratory distress in comparison with current practices of an S pO 2 frequently > 92% and oxygen flows ranging from 8 to 15 L/min. 8,9,10,15,19 In most cases, the frequent liberal use of oxygen leads to detrimental consequences, 6,7,9,11,14,17,[19][20][21][22] particularly in patients with trauma or respiratory distress and during myocardial infarction.…”
Section: Introductionmentioning
confidence: 89%
“…20 Very low S pO 2 are frequently encountered at altitude, and S pO 2 targets between 88% and 95% are recommended in mechanically ventilated patients with ARDS. 12,33 Although not recommended for all patients due to the lack of data, it was previously reported that moderate hypoxemia is safe for short-term exposure, even in the case of critically ill patients with septic shock. 34 There are mechanisms to compensate for acute hypoxemia and avoid cell hypoxia, such as increased cardiac output, vasodilatation, reduced cellular metabolism, and long-term mechanisms such as increased hemoglobin concentration.…”
Section: Impact Of the S Po 2 Target On Oxygenmentioning
confidence: 99%
See 1 more Smart Citation
“…13 The partial pressure of oxygen is 149 mm Hg at sea level, but 108 mm Hg at 8000 feet, resulting in a lower fraction of inspired oxygen. 14,15 This is sufficient for healthy individuals but frequently results in short events of hypoxemia (oxygen saturation <90%) in some patients, even though it remains unclear whether it may be injurious without a parenchymal brain lesion. 14,15 Therefore, a continued monitoring of oxygen saturation is necessary and an oxygen supplementation is required.…”
Section: Discussionmentioning
confidence: 99%
“…Research studies have identified potential negative effects of altitude on brain injuries, 8 suboptimal documentation of pain assessment and treatment during transport, 9 and more prevalent than expected hypoxemia during routine transports. 10 In addition, it has been found that low hemoglobin measures are not associated with adverse outcomes 11 and that the use of ketamine to manage pain in the en route care setting can be safe. 12 Despite the incremental advances that have been made, nurses in the acute care setting have an important perspective to identify potential problems or sources of error that could negatively affect patients and their recovery process.…”
mentioning
confidence: 99%